The myth of the lead arranger's share - Kristian Brickle; Quirin Fleckenstein; Sebastian Hillenbrand; Anthony Saunders (Federal Reserve Bank of New York, 2020)
We make use of Shared National Credit Program (SNC) data to examine syndicated loans in which the lead arranger retains no stake. We find that the lead arranger sells its entire loan share for 27 percent of term loans and 48 percent of Term B loans, typically shortly after syndication. In contrast to existing asymmetric information theories on the role of the lead share, we find that loans that are sold are less likely to become non-performing in the future. This result is robust to several different measures of loan performance and is reflected in subsequent secondary market prices. We explore syndicated loan underwriting risk as an alternative theory that may help explain this result.
Keywords: G21; G24; G30; 330; syndicated lending; loan sales; lead arranger